Carbonate reservoirs : porosity evolution and diagenesis in a sequence stratigraphic framework - Moore, Clyde H. (Developments in sedimentology, 2001)
Provides the reader with an integrated overview of diagenesis and porosity evolution in carbonate petroleum reservoirs and ancient carbonate rock sequences. This work is useful for advanced carbonate courses at graduate level, and a reference book for graduate students working with, or interested in, carbonate rock sequences and sediments.